2007
DOI: 10.1073/pnas.0608197104
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structures reveal a thiol protease-like catalytic triad in the C-terminal region ofPasteurella multocidatoxin

Abstract: Pasteurella multocida toxin (PMT), one of the virulence factors produced by the bacteria, exerts its toxicity by up-regulating various signaling cascades downstream of the heterotrimeric GTPases Gq and G12/13 in an unknown fashion. Here, we present the crystal structure of the C-terminal region (residues 575-1,285) of PMT, which carries an intracellularly active moiety. The overall structure of C-terminal region of PMT displays a Trojan horse-like shape, composed of three domains with a ''feet''-,''body''-, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
135
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(144 citation statements)
references
References 31 publications
7
135
0
2
Order By: Relevance
“…S6C). It has been shown that the positioning of the catalytic triad of PMT is very similar to the catalytic triad of papain and mainly deduced from this similarity PMT has been proposed to act as a protease (19). Our findings indicate that PMT acts as a deamidase to activate G proteins.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…S6C). It has been shown that the positioning of the catalytic triad of PMT is very similar to the catalytic triad of papain and mainly deduced from this similarity PMT has been proposed to act as a protease (19). Our findings indicate that PMT acts as a deamidase to activate G proteins.…”
Section: Discussionsupporting
confidence: 49%
“…Interestingly, PMT shares similarity with CNFs in the N-terminal binding and translocation domains. However, the C-terminal catalytic domain of CNFs has no obvious structural similarity with PMT, as evidenced by comparison of the crystal structure of the C-terminal C3 domain of PMT (19), harboring the minimal intracellular activity domain (20), with that of the catalytic domain of CNF1 (33) (Fig. S6 A and B).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This superfamily (Fig. S6) consisted of ChaN, a heme-binding protein from Campylobacter jejuni (32), the EreA-like esterase Bcr136 from Bacillus cereus (33), and a portion of the C2 domain of Pasteurella multocida dermonecrotic toxin (PMT) (34). Modeling of HopBA1-like P. syringae effector proteins revealed that the T3E HopB1 (Fig.…”
Section: Predicted Rba1 Dimer Interface Mutants Affect Both Function Andmentioning
confidence: 99%
“…The gene (toxA) encoding P. multocida toxin (PMT), 3 acquired by horizontal transmission (2), has been cloned and sequenced (3). It is a single polypeptide of 146 kDa whose C-terminal activity domain structure has been solved (4). In addition to its mitogenic properties for certain types of cells, including quiescent fibroblast and osteoclast cells, PMT is a strong inducer of anchorageindependent growth (5-7).…”
mentioning
confidence: 99%